MIAPS--programový systém pro odhadování poradí vzájemné podobnosti/nepodobnosti chování proteinů v case - Knízek, Jirí; Bergmann, Michal; Sindelár, Jan; Kovárová, Hana (Acta medica (Hradec Kralove). Supplementum, 2004)
Statistical order estimation of mutual similarity/dissimilarity of proteins' behavior in time is the main purpose of the programme system MIAPS. Comparing with Correspondence Analysis (CA) method, mostly used so far, is simultaneously performed. Time series of 2-DE maps are requested as the data. MIAPS is available on http://www.lfhk.cuni.cz/knizekj/ and http://www.utia.cas.cz/user_data/sindelar/miaps.htm.
Keywords: Electrophoresis, Gel, Two-Dimensional; software; Software; Proteins; 2D gelová elektroforéza; proteiny